1952
DOI: 10.1042/bj0510251
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of short-chain fatty acids in the sheep. 1. Fatty acid utilization and ketone body production by rumen epithelium and other tissues

Abstract: PSEUDO-CHOLINESTERASE ACTIVITY IN THE C.N.S. 251 must be stressed that these latter findings are of a preliminary nature and are as yet unsupported by any in vivo work, so that although we have evidence of an association of pseudo-cholinesterase activity with the white fibre tracts of the central nervous system we are at present unable to reach any conclusions as to its physiological function in these areas. SUMMARY 1. The relative rates of hydrolysis of a number of different choline esters by preparations fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
86
1
2

Year Published

1953
1953
1990
1990

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(96 citation statements)
references
References 7 publications
(7 reference statements)
7
86
1
2
Order By: Relevance
“…The proportion of butyrate reaching the venous blood stream is small in comparison to the proportion in the rumen (Kiddle, Marshall & Phillipson, 1951). Metabolism of butyric acid by the rumen epithelium (Pennington, 1952) and the production of ketone bodies by these tissues therefore is of considerable physiological significance. SUMMARY 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of butyrate reaching the venous blood stream is small in comparison to the proportion in the rumen (Kiddle, Marshall & Phillipson, 1951). Metabolism of butyric acid by the rumen epithelium (Pennington, 1952) and the production of ketone bodies by these tissues therefore is of considerable physiological significance. SUMMARY 1.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that more butyrate can be absorbed from the rumen than can be accounted for by the butyrate entering the blood stream (Masson & Phillipson, 1951), and this is due to metabolism of butyrate by the rumen epithelium (Pennington, 1952) which in vitro is more pronounced than metabolism of propionate or acetate. The experiments described here were designed to study (a) the absorption of these three acids quantitatively by introducing a steady inflow of a solution of these acids at a suitable pH and in amounts that would maintain the concentrations in the rumen at physiological levels, and (b) to see whether the information so gained could be used to determine the rates of absorption in unanaesthetized sheep that were fasting or feeding.…”
mentioning
confidence: 99%
“…5) Table 7 it has been assumed that the traces found in the rumen have appeared in proportion to the time. Pennington (1952) It is concluded that these acidic weak electrolyte movements will give rise to hydrogen-ion movements less than -1-0 m-mole/hr, and in most cases the possible contribution of ammonia to hydrogen-ion movements is less than 1-0 m-mole/hr.…”
Section: Gaseou8 C02 Exchangementioning
confidence: 99%
“…There is, however, a clear relationship between the concentration of acetate in the rumen and the venous-arterial differences, and the fact that the relationship is not linear is interesting, for it suggests that absorption is more efficient from weak solutions than from stronger ones. The losses of acetate in vitro due to metabolism by rumen epithelium are small compared with those for butyrate and propionate (Pennington, 1952), so that a relation can be expected between these two sets of values. Poisoning ofthe rumen epithelium by exposing it to 0X002 M-mercuric chloride inhibited absorption of the anions, acetate and chloride, while absorption of the cations, potassium and sodium, proceeded unhindered.…”
Section: Discussionmentioning
confidence: 93%